A human rights-focused HIV intervention for sex workers in Metro Manila, Philippines: evaluation of effects in a quantitative pilot study - Urada, Lianne A. (Int J Public Health, 2016)
OBJECTIVES: This study evaluated a brief human rights-focused HIV community mobilization intervention for sex workers in the Philippines, a country with one of the fastest rising number of HIV cases worldwide. METHODS: Five single-session group interventions to reduce sexual risk and increase HIV testing among 86 sex workers in Manila were evaluated with pre–post-test data via Wilcoxon’s signed-ranks and Mann–Whitney tests. The 4-h intervention, Kapihan (August–November, 2013), integrated human rights with HIV skill-building. Demographic data, violence/trafficking victimization, human rights knowledge, and intentions to HIV test and treat were collected. RESULTS: Participants were median aged 23; female (69 %); had children (55; 22 % had 3+ children); used drugs (past 3 months: 16 %); sexually/physically abused by clients (66 %); 20 % street sex workers ever took an HIV test. Pre–post-test scores significantly improved in knowledge of HIV (z = −8.895, p < 0.001), reproductive health (z = −3.850, p < 0.001), human rights (z = −4.391, p < 0.001), ethical rights of research participants (z = −5.081, p < 0.001), and intentions to HIV test (z = −4.868, p < 0.001). CONCLUSIONS: Integrating human rights into HIV interventions may empower sex workers to address their health and human rights and test for HIV.